Evaluation of alveolar bone level after orthodontic clear aligners treatment: A retrospective study - Mohammed Alasqah; Dalal Abdullah Alshammery; Mohammad Abdul Baseer; Hussah Aladwane; Abdulaziz Alsakr (Saudi Journal of Oral Sciences, 2024)
Introduction: Clear aligners have increased in popularity as an alternative to conventional fixed equipment in orthodontic treatment. However, the impact of clear aligner orthodontic therapy on the periodontium, particularly the periodontal tissues, has generated curiosity in research. Aim: This study aimed to evaluate the relationship between clear aligner orthodontic treatment and the height of the alveolar bone level. Materials and Method: Ninety-two panoramic radiographs (pretreatment and posttreatment) from 46 adult patients treated with clear aligner therapy were selected for the current study. Linear measurements have been performed in the panoramic radiographs to measure the alveolar bone. Patient data, including age, gender, type of malocclusion, duration of the orthodontic treatment, inter-proximal striping done or not during the orthodontic treatment, and changes in alveolar bone level in millimeters, were documented. Results and Discussion: Posttreatment significantly increased alveolar defects (p=<0.001). Moreover, the pretreatment and posttreatment alveolar bone defect was compared in different teeth that showed that significant difference in teeth #21(p=0.007), #17(p=0.006), #31(p<0.001), #32(p=0.011), #33(p =0.003), #41(p <0.001), #42(p =0.003) and #44(p<0.001), #45(p <0.001) and #46 (p=0.009). Comparison of pretreatment and posttreatment alveolar bone defects also showed significant differences in patients with interproximal striping (p=<0.001). Other variables exhibited no significant differences (p>0.05). Pretreatment and posttreatment mean differences in alveolar bone defects were statistically significant across all the studied variables (p<0.05) except in the Class III malocclusion (p=0.082). Moreover, there is a significant positive correlation observed between the age of the study participants and pretreatment (p=0.007) and posttreatment bone defects (p=0.002) along with pretreatment and posttreatment alveolar bone defect (p= <0.001). Conclusion: This study advances the understanding of the complexities surrounding malocclusion, clear aligner orthodontic treatment, and alveolar bone height.